The Influence of the Musical Rhythm according to the Interactive Method of Learning the Top-down Passing Skills in the Volleyball for Students - Saeed Gheni Noori (Journal of Global Pharma Technology, 2016)
The objective of the search is to identify the effectiveness of the use of musical tunes in the interactive method of learning the top-down passing skills in the volleyball, and the experimental method has been used to suit the nature of the problem. The research community has identified the fourth grade students of the Dar Al Salaam boys school in Misan governorate for the 2018-2017 school year, which totaled (72) students. (60) Students were randomly selected from the research community, who accounted for (83.3) of the community, and were divided into two groups, the control group was (30) students and the experimental group was (30) students. Thus, the researchers conducted parity between the two groups, and it took (5) weeks to implement the program by two educational units per week, and at a time of (45 minutes) per educational unit. The researchers used the method of application (SPSS) and some other statistical means. The researchers concluded the effectiveness of the program using the rhythms of music according to the method of exchange in learning the skills of passing up and down in the volleyball, and also concluded the speed in the acquisition of skills because of the adaptation of students with the program prepared for the duty sheet and feedback.Keywords: Music rhythm, Interactive mode, Skills of passing top and skill of passing from down.